(untitled) (Medicine Today, 2021)
Introduction: Posterior capsular opacification is caused by migration and proliferation of cuboidal epithelium from remnant of anterior capsule and equatorial part of the lens capsule. Posterior capsular opacification also called after cataract is a nagging post surgical complication following phacoemulsification or non phaco cataract surgery (small incision cataract surgery or conventional cataract surgery) ECCE with posterior chamber intraocular lens implantation. Posterior capsular opacification is actually misnomer. Though there are many factors suggested to reduced posterior capsular opacification. The incidence of PCO still exists considerably. Aims and Objective are to find out the visual improvement after Nd yag laser posterior capsulotomy. Materials and Methods: The prospective study was conducted in the department of ophthalmology of Ad-din Women Medical College Hospital, Dhaka, Bangladesh from June 2014 to June 2018. 175 patients of 189 eyes with significant PCO. Before laser capsulotomy all patients were assess by routine slit lamp examination, IOP measurement and posterior segment examination done for every patient for exclusion of Gross posterior segment pathology. Results: The study had female preponderance (58.86%). Most of the patients 165 were 40 to 80 years old (87.31%). The patients had pre laser visual acuity 6/9 to 6/18 (31.75%) 6/24 to <6/60 (68.25%). After laser capsulotomy functional visual acuity upto 6/8 were 169 (89.42%) and 6/24 to <6/60 were 20 (10.58%). The mean pre and post laser capsulotomy visual functional score were 54.45±36.44 and 94.16±50.36 respectively. Conclusion: Nd YAG laser capsulotomy is safe, non-invasive and effective procedure. Medicine Today 2021 Vol.33(2): 98-101